2020
DOI: 10.1111/dom.14122
|View full text |Cite
|
Sign up to set email alerts
|

Remission of type 2 diabetes following long‐term treatment with injectable testosterone undecanoate in patients with hypogonadism and type 2 diabetes: 11‐year data from a real‐world registry study

Abstract: Aims: To investigate whether testosterone therapy (TTh) in men with hypogonadism and type 2 diabetes mellitus (T2DM) improves glycaemic control and insulin sensitivity, and results in remission of T2DM. Material and Methods: A total of 356 men who had total testosterone levels ≤12.1 nmol/L (350 ng/dL) and symptoms of hypogonadism were included in the study and followed up for 11 years. All patients received standard diabetes treatment and 178 patients additionally received parenteral testosterone undecanoate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 48 publications
3
75
1
1
Order By: Relevance
“…As older men with T2DM are at greater risk of mortality from COVID-19, a therapy that potentially prevents progression to T2DM should also reduce the risk from COVID-19. 24,25 This approach is strongly endorsed by two recent review articles from Italy and the United States. 92,93 Current evidence-based guidelines from multiple medical disciplines already recommend screening, diagnosing, and treating men with hypogonadism in high-risk groups, such as type 2 diabetes, BMI >30 kg/m 2 , and men with ED.…”
Section: Uk Statistics For Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…As older men with T2DM are at greater risk of mortality from COVID-19, a therapy that potentially prevents progression to T2DM should also reduce the risk from COVID-19. 24,25 This approach is strongly endorsed by two recent review articles from Italy and the United States. 92,93 Current evidence-based guidelines from multiple medical disciplines already recommend screening, diagnosing, and treating men with hypogonadism in high-risk groups, such as type 2 diabetes, BMI >30 kg/m 2 , and men with ED.…”
Section: Uk Statistics For Type 2 Diabetesmentioning
confidence: 99%
“…23 Other articles have shown reversal of T2DM with TRT in a third of patients and reversal of prediabetes to normoglycemia compared with a control group. 24 A recent metaanalysis concluded that ''low testosterone levels in men with T2DM are associated with increased cardiovascular mortality'' and that ''testosterone therapy is associated with a reduction in all-cause mortality and cardiovascular events.'' 25 Recently a large multicenter randomized controlled trial (RCT) from Australia has been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Clinical Utility of TTh as a Treatment for Obesity: Long-Term RWE The RWE from long-term observational studies have provided compelling support for the use of TTh as a sustainable and feasible treatment for obesity. 42,[53][54][55][86][87][88][89][90][91][92][93] These observational studies comprise men with TD and various degrees of obesity and weight classes, ranging from normal weight to obesity class III, who are receiving long-term treatment with T undecanoate injections in real-life urology practices.…”
Section: Bidirectional Link Between Obesity and Tdmentioning
confidence: 99%
“…Another RWE analysis of 356 men with T2DM and TD examined whether long-term TTh can result in remission of T2DM. 92 Remission of T2DM was defined as HbA 1c <6.5% and discontinuation of all diabetes drugs, including metformin. All patients received standard T2DM treatment.…”
Section: Bidirectional Link Between Obesity and Tdmentioning
confidence: 99%